A regioselective Synthesis of Substituted Pyrazolines via a Cascade Annulation of Huisgen Zwitterion with α‐Cyano‐α, β‐unsaturated Ketones Under Solvent‐free Heating Conditions. Issue 35 (17th September 2019) - Li, Yuming; Zhang, Xuange; Lu, Tianyu; Miao, Zhiwei
Abstract: A simple solvent‐free method for the regioselective synthesis of pyrazoline derivatives via the annulation reactions of α‐cyano‐α, β‐unsaturated ketones and β‐carboxylic ester‐α, β‐unsaturated ketone with Huisgen zwitterions was developed. Interestingly, the reaction substrate is identified as a critical factor to control the final products. This method features simplicity, high efficiency, environmentally benign, and broad substrate scope. The gram scale applicability also points towards its possible implementation in industrial use. Abstract : A simple solvent‐free method for the regioselective synthesis of pyrazoline derivatives via the annulation reactions of α‐cyano‐α, β‐unsaturated ketones and β‐carboxylic ester‐α, β‐unsaturated ketone with Huisgen zwitterions was developed.